The role of consumer protection associations in rationalizing consumer purchasing behavior – an example of consumer research in the state of Ouargla - Afaf KHOUILED; Florin-Alexandru LUCA; Hicham MAHDJOUBA; Sami Mohammed BENNOUNA (Management Intercultural, 2023)

(untitled)
Movements and institutions concerned with consumer protection request to improve the standard of living of individuals and improve the quality of life for them. Consumerism among consumers, promoting them to keep pace with developments in various fields, raising their awareness of the risks that threaten their security and safety, and informing them of scientific, health and economic knowledge so that the consumer obtains his full rights without being exposed to fraud or marketing deception. Rationalizing consumer purchasing behavior, as this study was conducted on a sample of consumers in the state of Ouargla, and a questionnaire was used as a tool for the study, so the number of questionnaires used reached 200 forms), and the results showed that: There is a weak direct correlation estimated at (28%) between consumer protection associations purchasing behavior; The Consumer Protection Association played a weak role in providing targeted promotional programs to educate and rationalize consumers.